Case study: A CSCL approach for object-oriented programming learning - Flórez-Aristizábal, Leandro (2022)
A Computer-Supported Collaborative Learning (CSCL) approach was designed for the Systems Seminar course of the Systems Engineering program at University Antonio José Camacho (UNIAJC) in Cali (Colombia) [1]. The purpose was to make Object-Oriented Programming (OOP) learning not an individual process but a collective one where students play different roles to solve a software-based problem (from requirements specification to software development). Based on the results of the experts’ review made in the previous study, a case study is now proposed to assess the feasibility of this approach. Eight students took part of this study following each of the stages proposed in the approach and the results show that even though this is still a good starting point, some changes need to be made to achieve better results.